2020
DOI: 10.1371/journal.pone.0241567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topical application of 0.4% oxybuprocaine hydrochloride ophthalmic solution and 1% ropivacaine hydrochloride on corneal sensitivity in rats

Abstract: The aim of the present study was to determine and compare the degree and duration of corneal anesthesia following topical application of 0.4% oxybuprocaine hydrochloride ophthalmic solution and 1% ropivacaine hydrochloride treatment in healthy rats. A randomized, blinded, crossover study was conducted on 20 healthy adult Wistar rats, following complete physical and ophthalmological examination. Baseline corneal touch threshold (CTT) was determined in the central corneal area of both eyes with a Cochet–Bonnet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The role of rh EGF in epithelial healing after injury is signi cant and can signi cantly improve clinical symptoms in patients [32] . Oxibuprocaine hydrochloride, as a local anesthetic, acts rapidly on the branches of the trigeminal nerve by administration from the conjunctival sac, thereby inhibiting or temporarily blocking the transmission of nerve signals, thus providing an anesthetic effect on the conjunctiva, cornea, sclera, and iris [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…The role of rh EGF in epithelial healing after injury is signi cant and can signi cantly improve clinical symptoms in patients [32] . Oxibuprocaine hydrochloride, as a local anesthetic, acts rapidly on the branches of the trigeminal nerve by administration from the conjunctival sac, thereby inhibiting or temporarily blocking the transmission of nerve signals, thus providing an anesthetic effect on the conjunctiva, cornea, sclera, and iris [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the topical anesthetic-treated eyes in our study reported an average duration of anesthesia between 60 and 120 min after single-use application of the preservative-free oxybuprocaine, a finding that would help to reduce the need for frequent instillation described with tetracaine and proparacaine. The durability and less irritating adverse effects of topical oxybuprocaine hydrochloride 0.4% compared with other topical anesthetics have been shown in veterinary research studies [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local anaesthesia, 0.4% oxybuprocaine, is generally used for procedures involving the cornea, such as measuring the IOP, gonioscopy and removal of the foreign body, and may cause a reduction in IOP with GAT. 27,28,29 Diagnostic mydriatic agents are routinely used in most eye clinics; however, they can potentially increase IOP. 8,14,30 Furthermore, there is a paucity of similar studies in South Africa, including where there is measurement of CCT.…”
Section: Introductionmentioning
confidence: 99%